The dilemma of social media for German work councils representing qualified employees—the case of a German car manufacturer. (6th December 2020) - Staples, Ronald; Whittall, Michael
Abstract : The world of work is undergoing huge changes as a result of digitalisation. Part of this transformation process involves a growing demand for skilled employees—a section of the workforce that appears increasingly less reliant on the representative services provided by works councils. In the following article, we consider works council's use of ICT tools to re‐engage with skilled employees, noting that current institutional and cultural contingencies appear to hinder its employment of ICT tools.